A Comparative Study of Gadobutrol Relaxivity at 3 Tesla for Sustainable Contrast Management and Standardized Phantom Calibration - Ha’, Maheran Che; Kamal, Izdihar; Kechik, Mohd Mustafa Awang; Sayuti, Khairil Amir; Mohammed, Yusri; Karim, Muhammad Khalis Abdul; Doyan, Aris (AMPLITUDO : Journal of Science and Technology Innovation, 2026)
This study aimed to characterize the relaxivity profiles of pure agarose and gadobutrol in 1% (w/v) agarose under two experimental conditions (within the air and tap-water immersion). T1 and T2 values were quantified at 3 Tesla, Siemens, Vida scanner using inversion recovery turbo spin echo (IR-TSE) for T1 and multi-echo turbo spin echo (ME-TSE) for T2. Different concentration of agarose (0.2 – 4.0% w/v) and gadobutrol (0.5 – 6.0 mM) and their T1 and T2 value for each concentration were measured. Pure agarose demonstrated low longitudinal relaxivity (r1 » 0.04 - 0.05 s-1.(%w/v)-1 vs. r1 » 2.97 - 3.52 s-1mM-1) and high transverse relaxivity (r2 » 5.00 - 6.34 s-1.(%w/v)-1 vs. r2 » 3.80 - 4.55 s-1mM-1) compared to gadobutrol. Agarose showed a very high r2/r1 ratio (129.4-160.0) than gadobutrol (1.28-1.29), reflecting stronger gel-matrix effects on transverse dephasing than on longitudinal recovery. Tap-water immersion had shortened T1 by »9% relative to air, without significantly increasing variability. These findings provide relaxivity values for agarose and gadobutrol under well-defined conditions and illustrate how their complementary relaxation behavior can tune T1 and T2 values over a wide range to create customizable MRI calibration phantom for research and clinical use